2014
DOI: 10.1007/s12070-014-0755-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Review and Survival Characteristics of Adenoid Cystic Carcinoma

Abstract: To study the clinical characters, the outcomes of treatments and the factors affecting treatment results of adenoid cystic carcinomas at Shahid Sadoughi Hospital and Shahid Ramazanzadeh radiotherapy center, Yazd, Iran. The clinical data of 31 patients with adenoid cystic carcinoma of any anatomic site diagnosed over an 8 year period (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012), were investigated retrospectively. Data regarding patients' characteristics, pathological features and follow-up were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Disease progression was related with ACC, larger tumor size, and non-surgical treatment. It seems that ACC often has a positive margin even after surgical resection, because of the submucosal spread and perineural invasion that commonly extends beyond the visible tumor [8,10,22,23]. Previous studies have shown that complete resection and radical mediastinal nodal resection did not have a positive effect on survival in patients with ACC [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Disease progression was related with ACC, larger tumor size, and non-surgical treatment. It seems that ACC often has a positive margin even after surgical resection, because of the submucosal spread and perineural invasion that commonly extends beyond the visible tumor [8,10,22,23]. Previous studies have shown that complete resection and radical mediastinal nodal resection did not have a positive effect on survival in patients with ACC [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…ACC is a slow‐growing tumour generally with an aggressive behaviour and a peak incidence in the fifth to seventh decades of life . Reaching a correct cytologic diagnosis is often fraught with difficulties perhaps due to the enormous variability in the fine needle aspirate findings.…”
Section: Discussionmentioning
confidence: 99%
“…The preferred treatment for the majority of the patients is radical surgery with postoperative radiotherapy 6,8,9 . Due to the slow and persistent clinical course of ACC, patients may survive for years even after recurrence, and the overall survival rates at 2, 5 and 7 years have been reported to be 95%, 75% and 57%, respectively 10 . Many studies have focused on identifying specific prognostic factors for ACC, such as site of origin, tumor size, lymph nodes, distal metastases, clinical stage, solid histological pattern or histopathology grade, early or late diagnosis, the presence of affected surgical margins and macroscopic perineural invasion 11‐13 .…”
Section: Introductionmentioning
confidence: 99%